High-resolution Hg chemostratigraphy: A contribution to the distinction of chemical fingerprints of the Deccan volcanism and Cretaceous–Paleogene Boundary impact event - Sial, A. N. (2014)
There is a renewed interest in volcanism as the major trigger for dramatic climatic changes at the Cretaceous–Paleogene transition (KTB), which were accompanied by a decrease in biodiversity and mass extinction. We have used Hg contents as proxy for volcanic activity at the classical localities of Gubbio (Italy) and Stevns Klint (Denmark) where the KTB layer is easily recognizable, and at a near-complete succession exposed at the Bajada del Jagüel locality in the Neuquén Basin, Argentina. These three localities display similar δ13Ccarb trends with markedly negative excursion at the KTB layer. Bulk-rock oxygen isotopes yielded similar pathways across the KTB layers in these localities and, if considered near-primary, the negative δ18O excursion at the KTB in Gubbio and Bajada del Jagüel suggest warming temperatures during this transition, whereas the negative excursion immediately followed by positive one at Stevns Klint points to a cycle of warm followed by colder climate. At Stevns Klint, Hg contents reach 250 ng g− 1 within the KTB layer (Fiskeler Member) and 45 ng.g− 1 at 1.5 m above that, while within the Scaglia Rossa Formation at Gubbio, three Hg peaks across the KTB are observed, one of them within the KTB layer (5.3 ng g− 1). Hg shows several peaks across the KTB in the Neuquén Basin, with up to 400 ng g− 1 in the Jagüel Formation. The phenomena that caused dramatic changes at the KTB probably expelled huge amounts of Hg into the atmosphere as recorded by these high Hg levels. A co-variation between Hg and Al2O3 in the studied sections suggest that Hg is adsorbed onto clays. Hg concentrations and also Hg isotopes are perhaps a powerful tool in the assessment of the role of volcanic activity during extreme climatic and biotic events, and in assessing the role of meteorite impact versus volcanism as the predominant cause of past global catastrophes and mass extinction.